ANALISIS GAYA BELAJAR SISWA SECARA VISUAL, AUDITORI DAN KINESTETIK TERHADAP PRESTASI BELAJAR MATA PELAJARAN IPA - Jima, Maria Julita; Fitriah, Fitriah; Solo, Yuliana Dua (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This study aims to determine students' visual, audiotonal and kinesthetic learning styles on students' learning achievement, in class VIII B science subjects at SMP Negen 1 Mego. This research was conducted from 1 February to 28 February 2023. The method used is descriptive qualitative with percentages. Data collection was obtained through observation, questionnaires, interviews and documentation. From the analysis of visual, audiotonal and kinesthetic learning styles on student achievement that has been studied, the following results are obtained, visual learning styles during the learning process are included in the